2016
DOI: 10.4103/2152-7806.195587
|View full text |Cite
|
Sign up to set email alerts
|

"Next Door" intraoperative magnetic resonance imaging for awake craniotomy: Preliminary experience and technical note

Abstract: Background:During glioma surgery “maximal safe resection” must be the main goal. Intraoperative magnetic resonance imaging (iMRI) associated with awake craniotomy (AC) is a valuable tool to achieve this objective. In this article, AC with a “next-door” iMRI concept is described in a stepwise protocol.Methods:This is a retrospective analysis of 18 patients submitted to AC using iMRI; a stepwise protocol is also discussed.Results:The mean age was 41.7 years. Hemiparesis, aphasia, and seizures were the main initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…We thought the reason was that some studies did not only include GILAs but also may include gliomas of other eloquent areas. Such as Peruzzi 2011 [ 53 ], Pichierri 2019 [ 54 ], Tuominen 2013 [ 59 ], Ghinda 2016 [ 38 ], Mathias 2016 [ 46 ], Maldaun 2014 [ 45 ], Motomura 2017 [ 47 ] and Leon-Rojas 2020 [ 43 ], although these studies reported the incidences of TLD and PLD, the results may not reflect the real incidences because the inclusion of gliomas of other eloquent areas. The median PFS and OS of our cohort was longer than those of most cohorts in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…We thought the reason was that some studies did not only include GILAs but also may include gliomas of other eloquent areas. Such as Peruzzi 2011 [ 53 ], Pichierri 2019 [ 54 ], Tuominen 2013 [ 59 ], Ghinda 2016 [ 38 ], Mathias 2016 [ 46 ], Maldaun 2014 [ 45 ], Motomura 2017 [ 47 ] and Leon-Rojas 2020 [ 43 ], although these studies reported the incidences of TLD and PLD, the results may not reflect the real incidences because the inclusion of gliomas of other eloquent areas. The median PFS and OS of our cohort was longer than those of most cohorts in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the efficacy of the chosen method, we should observe its effect on adjacent tissue ( Ritaccio et al, 2018 ). Concerning speech tests, positive effects are expressed, for example, by anomalies in figure identification, speech arrest, aphasia, dysphasia, reverberation, and phonetic, phonemic or semantic paraphasia ( Bello et al, 2014 , Benzagmout et al, 2007 , Chang et al, 2015 , Duffau, 2011 , Duffau, 2015 , Hamer et al, 2012 , Mandonnet et al, 2017 , Mathias et al, 2016 , Ojemann and Whitaker, 1978 , Picht et al, 2013 , Riva et al, 2015 ). The effect ceases when the electrical stimulus is stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical mapping has greatly improved the outcome of brain surgeries. ( Beez et al, 2013 , Benzagmout et al, 2007 , Chang et al, 2015 , Duffau, 2010 , Duffau, 2011 , Hamer et al, 2012 , Mandonnet et al, 2017 , Mathias et al, 2016 ). The main goal in glioma surgeries is to try to achieve gross resection with as much safety as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-operative brain mapping using electrical stimulation is used by neurosurgeons to identify brain areas crucial for speech and language (Benzagmout et al, 2007; Chang et al, 2015; Duffau, 2010; Mandonnet et al, 2017; Mathias et al, 2016). The gold-standard approach identifies speech and language areas using electrical stimulation to elicit speech arrest, naming or other language difficulties (Duffau, 2010; Mathias et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Intra-operative brain mapping using electrical stimulation is used by neurosurgeons to identify brain areas crucial for speech and language (Benzagmout et al, 2007; Chang et al, 2015; Duffau, 2010; Mandonnet et al, 2017; Mathias et al, 2016). The gold-standard approach identifies speech and language areas using electrical stimulation to elicit speech arrest, naming or other language difficulties (Duffau, 2010; Mathias et al, 2016). However, because of the limited time in the operating room for patient brain mapping, there is considerable interest in developing pre-operative non-invasive brain stimulation (NIBS) approaches for speech and language brain mapping.…”
Section: Introductionmentioning
confidence: 99%